Desarrollo De indicadores de sostenibilidad ambiental en la Laguna del Quilotoa, Cantón Pujilí, Provincia de Cotopaxi. Propuesta de Conservación 2022. - Morales Tapia, Joselyn Lizeth (2022)
The present investigation takes the premise of the development of indicators of environmental sustainability that through the current diagnosis of the zone allows establishing indicators, emit mitigate the environmental impact in the locality, all with the purpose of presenting a proposal of environmental conservation with emphasis to the strengthening of the local eco-systemic development. The methodology used was based on the bibliographic analysis, to establish indicators of environmental sustainability is adapted to the deductive and inductive method that allows to determine the most appreciable information within the zone with which through the field phase is systematized in relation to the problematic generating an optimal answer of the premises established in the investigation such as the policies of conservation management, Nevertheless, the results obtained allow us to determine that the Quilotoa Lagoon is in a low state of affectation since the surveys provided to the inhabitants of the sector gave a percentage of a very good conservation with respect to the study area, however, there are environmental issues in which they have little or no knowledge that allows the natural development of the area as in other environments. In this way, the present investigation has allowed the establishment of environmental sustainability indicators with the purpose of being used by the entities in charge of its conservation and maintenance. Thus, the environmental sustainability indicators guarantee, face and evaluate necessary information that implies the balance of current and future needs of natural resources.